2003
DOI: 10.1046/j.1537-2995.2003.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radioisotope methods and a nonradioisotope method to measure the RBC volume and RBC survival in the baboon

Abstract: The greater in vivo elution of 51Cr, 111In-oxine, and 99mTc than that of biotin-X-NHS influenced the measurements of RBC volume, 24-hour posttransfusion survival, and life span of the fresh baboon RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 35 publications
2
26
2
Order By: Relevance
“…17 However, our MPL values are modestly shorter than those reported for stored human RBCs, which range from 103 to 116 days in adults, depending on the RBC-labeling method. 9,15,18,19 Because we performed a total of only eight studies (Table 1), the shorter MPL values may not reflect a genuine difference in posttransfusion survival compared with the results of others.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…17 However, our MPL values are modestly shorter than those reported for stored human RBCs, which range from 103 to 116 days in adults, depending on the RBC-labeling method. 9,15,18,19 Because we performed a total of only eight studies (Table 1), the shorter MPL values may not reflect a genuine difference in posttransfusion survival compared with the results of others.…”
Section: Discussioncontrasting
confidence: 54%
“…The difference may simply be a manifestation of the differences between results using biotinylated versus chromium-labeled RBCs. 17 Alternatively, because the posttransfusion survival studies reported by others were performed in adults, 9,15,18,19 our modestly shorter MPL values may be related to an undefined in-vivo factor unique to infants.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Comparable procedures have been optimized in mice using in vivo biotinylation to quantify erythrocyte removal during the course of experimental infection with rodent malaria parasites (28) but not, to our knowledge, in naïve or malaria-infected nonhuman primates. Methodologies to quantify the erythrocyte life span in nonhuman primates have usually involved the autotransfusion of in vitro-labeled cells (29).…”
Section: Resultsmentioning
confidence: 99%
“…Blood was collected 1 h after the bypass procedure, labeled with 51-Cr, and autotransfused to measure the 24-h post-transfusion survival. 7,8 …”
Section: Introductionmentioning
confidence: 99%